2016
DOI: 10.1177/1534484316639713
|View full text |Cite
|
Sign up to set email alerts
|

Complexity and Organizational Communication

Abstract: In recent years, a growing body of literature has emerged from the intersection of complex systems science and organizational communication. However, due to the incoherence and immaturity of complexity science, this body of research is slightly disorganized. This article explores this research node using a meta-paradigmatic framework to untangle and clarify the different paradigmatic assumptions in the field of organizational communication research that has adopted the complexity science perspective. Our analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…Taking charge can only be achieved if strong climates for psychological safety exist in the organization, and for people to feel comfortable engaging in taking charge without fear of ridicule or punishment, managers must work to create a climate of psychological safety. For instance, the complexity lens implies that error-free systems are too rigid to coevolve with the environment [67]. Hence, managers should be deeply aware of the role of failure in organizational learning and adaptation and enhance psychological safety by building a corporate culture that embraces failure.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Taking charge can only be achieved if strong climates for psychological safety exist in the organization, and for people to feel comfortable engaging in taking charge without fear of ridicule or punishment, managers must work to create a climate of psychological safety. For instance, the complexity lens implies that error-free systems are too rigid to coevolve with the environment [67]. Hence, managers should be deeply aware of the role of failure in organizational learning and adaptation and enhance psychological safety by building a corporate culture that embraces failure.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…As individuals who come from rural areas, grassroots innovators have a complex socio-cultural system and their characters compromise the social, environmental, and economic contexts to be locally embedded in their innovative solutions, which requires high thinking order and skillset. In the study conducted by Poutanen and Soliman (2015), embracing complexity is among the vital lessons learnt for the system to evolve or coevolve to be able to meet the social, environmental, and economic needs at large. They further confirmed that the application of the complexity theory to innovation has yet to be tested.…”
Section: H6 Relative Advantage Is the Predictor Of Internet Of Things (Iot) Usage G Complexity And Internet Of Things (Iot) Usagementioning
confidence: 99%
“…Broadly construed, two types of methods can be used to investigate complex phenomena. The first approach to complexity research is labeled the narrative (Tsoukas & Hatch, 2001), or interpretive, approach (Poutanen, Siira, & Aula, 2016). This approach focuses on storytelling, subjectivity, and searching for meaning (Poutanen et al, 2016;Tsoukas & Hatch, 2001).…”
Section: The Researcher's Toolkit: Finding the Fingerprints Of Comple...mentioning
confidence: 99%
“…The first approach to complexity research is labeled the narrative (Tsoukas & Hatch, 2001), or interpretive, approach (Poutanen, Siira, & Aula, 2016). This approach focuses on storytelling, subjectivity, and searching for meaning (Poutanen et al, 2016;Tsoukas & Hatch, 2001). Research conducted through this approach is contextualized and grounded in a historical, narrative account (Poutanen et al, 2016;Tsoukas & Hatch, 2001).…”
Section: The Researcher's Toolkit: Finding the Fingerprints Of Comple...mentioning
confidence: 99%
See 1 more Smart Citation